Recycled Household Ash in Rice Paddies of Bangladesh for Sustainable Production of Rice Without Altering Grain Arsenic and Cadmium - Gupta, Yogesh (2023)
In Bangladesh most agronomic biomass (straw, husk, dried dung) is burnt for domestic cooking use. Consequently, the soil is continuously stripped of mineral nutrients and carbon (C) substrate. QueryHere we investigate if recycling of household ash (ash) as fertilizer can sustainably improve soil fertility as well as minimise accumulation of toxic elements (As, Cd) in rice grain. Large scale field trials across two geographic regions (Barind, Madhupur) and two seasons (wet, dry) and with application of 3 fertiliser treatments (NPKS, ash, NPKS + ash) were conducted. At the end of each season, the impact of region*season*treatment on soil microbial comunities, rice yield, and grain quality (As, Cd, nutrient elements) was assessed. When compared to conventional field application rates of NPKS (control), application of ash boosted rice yield by circa. 20% in both regions during wet and dry season, with no effect on rice grain carcinogenic inorganic arsenic (iAs), dimethylarsonic acid (DMA) or cadmium (Cd), but with potential to increase zinc (Zn). For soil microbial communities, a significant region and season effect as well as correlation with elements in rice grain was observed, amongst these Cd, Zn, iAs and DMA. This study illustrates that application of ash can reduce the requirement for expensive chemical fertiliser, whilst at the same time increasing rice yield and maintaining grain quality, making farming in Bangladesh more sustainable and productive. The study also implies that the combined impact of region, season, and soil microbes determines accumulation of elements in rice grain.